Analysis of Genetic Polymorphisms as Risk Factors in Essential Hypertension and Type 2 Diabetes Mellitus among Malaysians - Vasudevan, R. (2009)

(untitled)
Genetic Polymorphisms are the variations found in the DNA sequences and they are integral to the development of genetic markers to identify individuals at risk. The genotypic distribution of various genetic polymorphisms involved in essential hypertension (EHT) and type 2 diabetes mellitus subjects (T2DM) has been established in many populations with conflicting results but in Malaysian subjects it has not been well characterized. The main objective of this study was to determine the association of various polymorphisms involved in the renin angiotensinaldosterone system (RAAS), insulin receptor, lipoprotein lipase, interleukin gene and G protein ß 3 subunit genes in EHT and T2DM of Malaysian subjects. This crosssectional study includes 70 EHT without T2DM, 60 T2DM, 65 EHT with T2DM and 75 unrelated healthy control subjects. Genomic DNA was extracted from the peripheral blood and the plasma was separated and analyzed for the biochemical analyses. The genotypes of the various genetic polymorphisms were determined using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), mutagenically PCR and the hot-start PCR methods. All PCR products and the restricted fragments were resolved electrophoretically on agarose and polyacrylamide gels. Statistical analyses was done using SPPS version 14.0. The baseline characteristics such as age, body mass index, diastolic blood pressure, fasting plasma glucose, high density lipoprotein cholesterol and sodium differed significantly (p<0.05) in case subjects compared to control subjects but not in low density lipoprotein cholesterol, total cholesterol and potassium. The insertion/deletion (I/D) and G2350A polymorphism of the angiotensin converting enzyme (ACE) gene and the I/D polymorphism of the alpha adrenoceptor gene differed significantly in EHT and T2DM subjects, whereas the A6G variant of the angiotensinogen (AGT) gene differed significantly (p<0.05) in the EHT and EHT+T2DM subjects when compared to the control subjects but not in the T2DM subjects. However, the BglI and MboI polymorphisms of the renin gene, the A6244G polymorphism of the insulin receptor gene, the S477X polymorphism of the lipoprotein lipase gene, the C511T polymorphism of the interleukin gene and the C825T polymorphism of the G protein ß 3 subunit genes did not differ significantly (p>0.05) when compared to the control subjects. Therefore, the polymorphisms of ACE, AGT and alpha adrenoceptor genes involved in RAAS were significantly associated with EHT and T2DM in Malaysian subjects. The genotypes and alleles of those polymorphisms can be considered as possible genetic markers or predisposing risk factors for EHT and T2DM in Malaysian subjects.